2015
DOI: 10.1063/1.4918365
|View full text |Cite
|
Sign up to set email alerts
|

Energy dissipation channels affecting photoluminescence from resonantly excited Er3+ ions doped in epitaxial ZnO host films

Abstract: Investigation of ZnO thin films deposited on ferromagnetic metallic buffer layer by molecular beam epitaxy toward realization of ZnO-based magnetic tunneling junctions J. Appl. Phys. 113, 17C106 (2013); 10.1063/1.4794875Microstructural compositional, and optical characterization of GaN grown by metal organic vapor phase epitaxy on ZnO epilayersWe identified prerequisite conditions to obtain intense photoluminescence at 1.54 lm from Er 3þ ions doped in ZnO host crystals. The epitaxial ZnO:Er films were grown on… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
4
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 11 publications
(4 citation statements)
references
References 38 publications
0
4
0
Order By: Relevance
“…The crystallinity of epitaxial films provides a near perfect crystal, but the maintenance of stoichiometry is still a challenge. At higher deposition rates, sputtering also provides suitable thin films, mainly polycrystalline, which the management of stoichiometry can be achieved by atmosphere control including oxygen [12,13]. Alternative techniques like sol-gel associated to dip-coating and spray pyrolysis can also be employed to thin film production avoiding the requirement of vacuum control and also producing polycrystalline films.…”
Section: Introductionmentioning
confidence: 99%
“…The crystallinity of epitaxial films provides a near perfect crystal, but the maintenance of stoichiometry is still a challenge. At higher deposition rates, sputtering also provides suitable thin films, mainly polycrystalline, which the management of stoichiometry can be achieved by atmosphere control including oxygen [12,13]. Alternative techniques like sol-gel associated to dip-coating and spray pyrolysis can also be employed to thin film production avoiding the requirement of vacuum control and also producing polycrystalline films.…”
Section: Introductionmentioning
confidence: 99%
“…For the LED with the ZnO:Er film, as shown in Figure e,g, the Er 3+ ions are seriously segregated in the region (∼5 nm thick) near the ZnO/SiO 2 interface, with a peak concentration of ∼7%. Then, the luminescence from such segregated Er 3+ ions with a considerably high concentration is believed to suffer from a serious concentration quenching effect, according to the results of previous reports. , Moreover, the hot electrons lose their energies significantly due to the impact on numerous Er 3+ ions in the segregated region near the ZnO/SiO 2 interface. In other words, the hot electrons which can be transported to the interior of the ZnO:Er film are dramatically decreased, resulting in much less excited Er 3+ ions.…”
Section: Resultsmentioning
confidence: 80%
“…Herein, the interior of the ZnO:Er film primarily refers to the region with the width equivalent to the mean free path of hot electrons in ZnO, which may be tentatively estimated to be ∼30 nm, referring to the Monte Carlo calculation results . Regarding the LED with the ZnO:(Ti, Er) film, as displayed in Figure f,h, the Er-segregation near the ZnO/SiO 2 interface is quite small with a peak concentration of ∼2%, which will not result in the concentration quenching effect. , Moreover, as elucidated above, a little bit more Er 3+ ions are incorporated into the ZnO matrix. Under the circumstances, the quenching of Er 3+ -related emissions and the significant loss of energy of the hot electrons hardly occur near the ZnO/SiO 2 interface within the LED with the ZnO:(Ti, Er) film.…”
Section: Resultsmentioning
confidence: 94%
“…The DLE band was found to be a broad and asymmetric photoluminescence band. H. Akazawa et al [31] identified the conditions to obtain strong photoluminescence intensity in a matrix of ZnO crystals doped with Er ions. The samples were synthesized using the sputtering method and heat treated.…”
mentioning
confidence: 99%